Immunological Aspects of Chronic Rhinosinusitis - Katarzyna Czerwaty; Katarzyna Piszczatowska; Jacek Brzost; Nils Ludwig; Mirosław J. Szczepański; Karolina Dżaman (Diagnostics, 2022)
Chronic rhinosinusitis (CRS) is related to persistent inflammation with a dysfunctional relationship between environmental agents and the host immune system. Disturbances in the functioning of the sinus mucosa lead to common clinical symptoms. The major processes involved in the pathogenesis of CRS include airway epithelial dysfunctions that are influenced by external and host-derived factors which activate multiple immunological mechanisms. The molecular bases for CRS remain unclear, although some factors commonly correspond to the disease: bacterial, fungal and viral infections, comorbidity diseases, genetic dysfunctions, and immunodeficiency. Additionally, air pollution leads increased severity of symptoms. CRS is a heterogeneous group of sinus diseases with different clinical courses and response to treatment. Immunological pathways vary depending on the endotype or genotype of the patient. The recent knowledge expansion into mechanisms underlying the pathogenesis of CRS is leading to a steadily increasing significance of precision medicine in the treatment of CRS. The purpose of this review is to summarize the current state of knowledge regarding the immunological aspects of CRS, which are essential for ensuring more effective treatment strategies.